2016
DOI: 10.1104/pp.16.01365
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Gene Silencing Maintained by OTS1 SUMO Protease Requires a DNA-Dependent Polymerase V-Dependent Pathway

Abstract: The expression of genes with aberrant structure is prevented at both the transcriptional and posttranscriptional regulation levels. Aberrant gene silencing at the posttranscriptional level is well studied; however, it is not well understood how aberrant genes are silenced at the transcriptional level. In this study, through genetic screening a transgenic report line that harbors an aberrant gene (35S-LUC, lacking 39-untranslated region [39-UTR]) and lacks luciferase (LUC) activity, we identify that the small u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…SUMOylation is implicated in the regulation of abiotic/biotic stress and hormone responses, various developmental processes, metabolism, chromatin remodeling, and transcriptional gene silencing in plants (Park et al ; Park and Yun ; Han et al ; Liu et al ; Zhang et al ). Various components of the SUMO system have been shown to regulate ABA signaling, indicating the importance of SUMOylation in the regulation of ABA signaling.…”
Section: Introductionmentioning
confidence: 99%
“…SUMOylation is implicated in the regulation of abiotic/biotic stress and hormone responses, various developmental processes, metabolism, chromatin remodeling, and transcriptional gene silencing in plants (Park et al ; Park and Yun ; Han et al ; Liu et al ; Zhang et al ). Various components of the SUMO system have been shown to regulate ABA signaling, indicating the importance of SUMOylation in the regulation of ABA signaling.…”
Section: Introductionmentioning
confidence: 99%
“…The spf1 spf2 ULP double mutants exhibit reduced seed set and self-fertilization [10,11]. A similar phenomenon is observed in ots1 ots2 ULP mutants [12,13]. Studies using loss-of-function mutants of E3 ligase have identified many SUMO substrates involved in nutrient homeostasis, signaling by hormones (gibberellins (GA), SA, abscisic acid (ABA)), light-sensing, stem cell maintenance, and the photoperiodic control of flowering [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 79%
“…For example, ESD4 was found to participate in the regulation of flowering of Arabidopsis [57]. AtSPF1/2 regulate female/male gamete and embryonic development [10,11], and OTS1/2 regulate the growth and salt stress responses in rice [12,24]. The SUMO protease family genes had low levels of expression during in almost all developmental stages, except Ad/ AiFUG1 and Ad/AiSPF1 were relatively higher expressed in shoot tip, suggesting their potential roles in shoot tip development.…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis thaliana ecotype Columbia‐0 (Col‐0) was used as the WT in all experiments. The mutants ots1‐2 (GK‐207D11, with a T‐DNA insertion in the sixth exon of At1g60220), abi5‐8 (SALK_013163, with a T‐DNA insertion in the 5’‐UTR of At2g36270), and myb30‐2 (with a T‐DNA insertion in the first exon of At3g28910) were obtained from ABRC; ots1‐3 (containing a G‐to‐A mutation at the last nucleotide in the eighth intron of At1g60220) (Liu et al ) was kindly provided by Dr. Yan Guo from China Agricultural University.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical significance was determined by Student's t-test; significant differences are indicated by an asterisk ( Ã , P 0.05). At1g60220) (Liu et al 2016) was kindly provided by Dr. Yan Guo from China Agricultural University.…”
Section: Plant Materialsmentioning
confidence: 99%